Convívio de estudantes na Cidade Universitária - Artur Pinto
1-Maria Otília; 2-Maria José Belbute (Letras); 3-Maria José Caeiro (Letras); 4-Alexandre Oliveira; 5-João Paradela (Medicina); 6-António Russo Dias.